2023
DOI: 10.3390/informatics10020041
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Boundaries of Success: A Literature Review and Research Agenda on Resource, Complementary, and Ecological Boundaries in Digital Platform Business Model Innovation

Abstract: Digital platform business model innovation is a rapidly evolving field, yet the literature on resource, complementary, and ecological boundaries remains limited, leaving a significant gap in our understanding of the factors that shape the success of these platforms. This paper explores the mechanisms by which digital platforms enable business model innovation, a topic of significant theoretical and practical importance that has yet to be fully examined. Through a review of the existing literature and an examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 106 publications
0
1
0
Order By: Relevance
“…Research on the field has suggested that established firms relied on the factors under their control, such as superior technology infrastructure, first-mover advantage, incentives, and subsidies, creation of social forums, and platform scope to attract participants, solve the early-stage conundrum of platforms, and trigger the network effect (Murthy & Madhok, 2021). Several studies indicate that platforms innovate or evolve in the dimensions that are related to the platform scope and are under the control of the firm (Baber et al, 2019;Berkers et al, 2020;Daradkeh, 2023;Foss & Saebi, 2017;Jovanovic et al, 2022).…”
Section: Platform Business Model (Pbm)mentioning
confidence: 99%
“…Research on the field has suggested that established firms relied on the factors under their control, such as superior technology infrastructure, first-mover advantage, incentives, and subsidies, creation of social forums, and platform scope to attract participants, solve the early-stage conundrum of platforms, and trigger the network effect (Murthy & Madhok, 2021). Several studies indicate that platforms innovate or evolve in the dimensions that are related to the platform scope and are under the control of the firm (Baber et al, 2019;Berkers et al, 2020;Daradkeh, 2023;Foss & Saebi, 2017;Jovanovic et al, 2022).…”
Section: Platform Business Model (Pbm)mentioning
confidence: 99%